Farelo de palma forrageira (Nopalea cochenillifera Salm Dyck) na dieta de equinos. - Garcez, Diana Silva Maynard (2016)
The author of this study aimed to evaluating the use of the cactus meal (Nopalea cochenillifera Salm Dyck) in horses diet. The first experiment was divided into two step: the first was the preference test between treatments with 0, 5, 10 and 15% replacement of pelletized concentrate by cactus meal (CM) on the diet, and the second step was the replacement of the ground concentrate by the same levels of CM. For both steps were used 10 Mangalarga Marchador mares, with a body weight of 355 ± 25 kg and age 10 ± 4 years. The experimental period consisted of three days of adaptation, where animals received 1.2 kg of commercial concentrated and three days of observation where the animals received 300g of commercial concentrate before testing and 300g of each treatment for 15 minutes. In step 1 was determined the rate of intake (RI). In steps 1 and 2 was performed the sorting test to classify diets in descending order of palatability. The experimental delineation used was entirely randomized and the intake rate data were submitted for variance analysis and regression at 5% of significance. The sorting test was statistically evaluated by Friedman test. Based on the RI, the animals showed higher preference for controlled diet while the treatment with 15% of CM was least consumed. According to the sorting test, in step one the most palatable feed was the treatment with no CM and feed with 5% of CM followed by the treatments with 15% and 10% substitution, in step 2 there was no difference in the palatability of the experimental diets. The second experiment evaluated feed intake, apparent digestibility and postprandial glycemic response of these treatments. Four mixed breed horses were used, aging 13 ± 2 years old and weighing 449 ± 15 kg. The diets consisted of Tifton 85 hay (Cynodon spp) and commercial concentrate on the proportion of 70:30, respectively. To determine the digestibility coefficients was carried out total collection of faeces. For the glycemic tests, 5 mL of blood were collected around 30 minutes before, and 30, 60, 90, 120, 180, 240 minutes after the treatments suply. The experimental delineation used was entirely randomized in Latin Square (4x4). Data were submitted for variance analysis and regression with 5% of significance. Feed intake of mineral matter and ether extract differed between treatments (P <0.05). Feed intake and digestibility of the other nutrients did not differ between treatments (P> 0.05). The basal glucose concentration, time until glucose peak and glucose peak concentration were similar among treatments, except for the 180-minute period. Thus, it can be concluded that the CM is an alternate feed in the diet of horses which can replace the concentrated feed in up to 15% without reducing the consumption and impair the digestibility of the diet, besides having great acceptance by the animals when mixed with feed ground.